Identifying the Causes of Learning Difficulties in Mathematics among Primary School Students (Journal of Education and Educational Development, 2024)
A variety of factors are associated with the learning difficulty in mathematics in the context of Pakistani schools. This study explored the different causes of learning difficulties in mathematics faced by primary school students in Karachi, Pakistan. Using a quantitative research design, the data was gathered from the parents and teachers of primary-going students in Karachi. The data was gathered using an adapted questionnaire having demographic and construct sections. The constructs were adopted by reviewing the literature. The findings of the study reveal a significant effect of Mathematics Efficacy, Grade Anxiety, Future Factors and Confidence level of students on their mathematic performance in classrooms. The study recommends that teachers serving to teach mathematics to primary school students consider the explored factors while preparing the lesson plans. This study contributes into the existing literature in terms of the impotence of increasing teachers’ awareness regarding the preparation of lesson plans having the source of fun and enjoyment in the classroom, as enjoyable mathematics learning increases the motivation of students to keep their future enjoyment in the mathematics tasks.